Effect of provider-selected order indications on appropriateness of antimicrobial orders in a pediatric hospital. (15th February 2018) - Nomura, Yosuke; Garcia, Madeleine; Child, Jason; Hurst, Amanda L.; Hyman, Daniel; Poppy, Amy; Palmer, Claire; Ranade, Daksha; Pyle, Laura; Parker, Sarah K.
Abstract : Purpose: The effect of mandatory provider-selected order indications (PSOIs) on appropriateness of antimicrobial ordering in a tertiary pediatric hospital was evaluated. Methods: Mandatory PSOIs for 14 antimicrobials were implemented in September 2013. Data on initial and final orders in the first 24 hours after ordering were collected from the electronic medical record. Orders from pre-PSOI and post-PSOI implementation were randomly selected and compared with documentation at the time of order to elicit the documentation-determined clinical indication (DDCI). Appropriateness of the order for the DDCI was evaluated and compared between groups using 2-sample t tests, chi-square tests, and logistic regression. Results: Among the total 1, 304 orders included in the review, 275 (21.1%) were inappropriate based on DDCI. The indications associated with the greatest number of inappropriate orders in both groups were suspected sepsis/bacteremia, meningitis/central nervous system infection, and pneumonia. A total of 128 (18.3%) of 700 initial orders were inappropriate compared with the DDCI in the pre-PSOI period, and 82 (17.8%) of 461 initial orders were inappropriate in the post-PSOI period ( p = 0.83). A total of 78 (11.1%) of 700 final orders were inappropriate in the pre-PSOI period, and 29 (6.3%) of 461 final orders were inappropriate in the post-intervention period ( p = 0.01). Overall, 84 (12%) of 700 inappropriate orders reached the patient in the pre-PSOI period versus 43 (9.3%) of 461 inappropriate orders in the post-PSOI period ( p = 0.15). Conclusion: PSOIs were effective in reducing inappropriate antimicrobial orders in the first 24 hours after ordering if the correct indication was selected.